Who is a Child and Who Can a Child Become: Recalling the Educational and Pro-social Achievements of Father Franciszek Blachnicki - Alicja Żywczok (Jagiellonian University Press, 2024)
The subject of the study described in this article is primarily the perception of a child by Father Franciszek Blachnicki (1921-1987), the founder of the Light-Life Movement, the Crusade for the Liberation of Man, and the Christian Service for the Liberation of Nations, among others. Based on an analysis of the works of this educator and theologian, his vision of childhood is also outlined. The research results have been supported by an appropriate structure for the article, which describes the methodological basis, places the research problems among the disciplines and subdisciplines of science, provides the basic concepts, and portrays Blachnicki in a broader historical context. The article also resolves research problems concerning his perception of a child and childhood (following the teachings of the Catholic Church) and his educational, pro-social and ethical suggestions addressed to contemporary people and found in his works.